Adaptive resource management for downlink OFDMA system with imperfect CSI. Issue 7 (1st March 2014) - Wang, Zhuwei; Liu, Lihan
Abstract : The effect of the imperfect channel state information (CSI) on the system performance of radio resource management is addressed for a downlink OFDMA system. Differing from the previous works, it is shown that the imperfect CSI introduces a signal‐and‐power dependent noise term, and then a new method is proposed to evaluate the utility function. Numerical simulations show that the signal‐and‐power dependent noise yields a non‐negligible degradation to the system performance.